The Essence of Human Beings as Social Beings in Islamic Views - Salastia Paramita Nurhuda, Nasichcah, Aisyah Karimah (GLOBAL SCIENTS PUBLISHER, 2024)
The title of this journal is The Nature of Humans as Social Beings in the Islamic View, namely humans as the most perfect creatures that Allah created should be able to know why and what our essence was created and what we should do as servants of Allah, Allah created humans with the aim of being caliphs on earth with the creation of human beings in the form of reason is what distinguishes humans from other creatures with the privilege that humans should be able to think, believe and fear God, carry out God's commands and stay away from what is forbidden. Humans are the most perfect creation of Allah SWT. He is a creature that has various abilities, especially the ability to communicate with other humans. With this ability, humans are said to be social beings. Humans themselves are said in the Qur'an as Al-Insan, Bani Adam, and Al-Basyar. Al-insan which means humans are social beings, namely humans are creatures of nations and tribes, he has the ability to get acquainted with other humans.